Epidemiology of Childhood Onset Essential Hypertension. (December 2018) - Gupta-Malhotra, Monesha; Shete, Sanjay; Barratt, Michelle; Milewicz, Dianna; Hashmi, Syed
Abstract The knowledge of epidemiology of a disease is paramount in identifying preventive measures. Currently there is a paucity of literature on the epidemiologic determinants of childhood onset essential hypertension (EH). We evaluated children with EH, ascertained in a rigorous manner, in a large multiethnic population in a tertiary pediatric hypertension clinic. We enrolled children with and without EH and obtained data by in-person interview of their parents and by direct anthropometric measurements including blood pressures. A total of 148 children (76 hypertension probands, 72 control probands, and males 53%, mean age 12.2 ± 4.3 years) were enrolled. Of these 148 children, 51 pairs were matched 1:1 on ethnicity, gender and age (±2.5 years). In this study we evaluated the demographics, genetic predisposition and a variety of exposures including, socioeconomic, perinatal, lifestyle and environmental, between cases and controls. All measures were similar between cases and controls other than a significantly higher BMI (p  = 0.01) and rates of obesity (p  = 0.03), and a difference of near-significance in any family history of EH (p  = 0.05) higher in cases compared to controls. The odds of obesity was 3.5 times higher among cases than controls. In this study, we evaluated a variety of prenatal and postnatal exposures that could potentially contributed to the EH phenotype in childhood. The findings of the study elucidate the epidemiology of EH in children and two important associated risk factors, any family history of hypertension and a higher body weight.